Efficiency of Cyperus alternifolius, Typha latifolia, and Juncus inflexus in the removal of nitrate from surface water - E. Ghamary (IWA Publishing, 2021)
Nitrate is one of the most toxic and pathogenic substances in drinking water. Nitrate levels have increased significantly in groundwater and surface water because of the high usage of nitrogenous fertilizers, which have lethal effects on human health. Therefore, the removal of this toxic material from surface water is absolutely essential. The goal of this paper is to evaluate the efficiency of three aquatic plant species, called Cyperus alternifolius, Typha latifolia, and Juncus inflexus, in the removal of nitrate from surface water. This experiment has been carried out in the laboratory scale using a hydroponics method. To do this, the water samples containing nitrate were collected and evaluated before and after the treatment to see the effects of these three plants on both the nitrate removal and the pH variation of water. The results show that all the plants can remove excessive levels of nitrate from the surface water. The comparison of the results has revealed that T. latifolia plant has higher ability to remove nitrate from water than C. alternifolius and J. inflexus. It was observed that the nitrate removal efficiency of T. latifolia was 95%, J. inflexus was 85%, and C. alternifolius was 70% after 10 days. Moreover, it was observed that the pH values of the treated water have been affected by these plants. The results of this study can be employed for further improvement of surface water quality, thereby lowering water purification time and costs as well as decreasing the nitrate-related diseases significantly. HIGHLIGHTS Typha latifolia, Cyperus alternifolius, and Juncus inflexus plants can remove the excessive levels of nitrate from the surface water.; C. alternifolius plant slightly decreases the pH value of water after 10 days.; J. inflexus and T. latifolia plants increase the pH value of water.;